2015
DOI: 10.17140/aftnsoj-se-1-108
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Rice Genetic Resources for Food Security

Abstract: In the Philippines, rice is a primary agricultural crop and major caloric food source of Filipinos. Rice is produced in all of this archipelagic country's provinces, wherein total production (~18.4 million MT) is ranked eighth in the world. PhilRice was established as a dedicated research and development arm to propel sustained rice yield growth and stability toward selfsufficient production. Supporting its rice varietal improvement program is its Gene bank, a national repository of local-and foreign-sourced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Although genebanks exist as germplasm repositories, farmers and farmers' groups, or organizations also exert efforts to save seeds of crop species and have been custodians of landraces and traditional varieties as well [7,8]. Additionally, genebanks exist to conserve the genetic diversity of wild and cultivated plants that people rely on as a source of food, fuel, and fiber [3].…”
Section: Germplasm Banks and Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although genebanks exist as germplasm repositories, farmers and farmers' groups, or organizations also exert efforts to save seeds of crop species and have been custodians of landraces and traditional varieties as well [7,8]. Additionally, genebanks exist to conserve the genetic diversity of wild and cultivated plants that people rely on as a source of food, fuel, and fiber [3].…”
Section: Germplasm Banks and Functionsmentioning
confidence: 99%
“…Smallholder farmers have contributed to and unknowingly preserved the diversity of rice genetic resources throughout time as they cultivated, selected, and nurture their favorite cultivars owing to favorable yield and quality of product. These cultivars comprised of landraces and traditional varieties are vast sources of important genetic traits that can further improve future rice varieties [8]. Historical accounts on rice breeding, for instance, show the discovery and development of high-yielding cultivars that can withstand environmental stresses, such as varieties having excellent genes for submergence tolerance and having significant yield increases owing to NAL1 allele [8].…”
Section: Importance Of Rice Genetic Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that landraces and traditional cultivated rice varieties collected from farmers have considerable phenotypic variabilities ( Figure 4A) and tolerance to drought and high temperature (Ferrer, 2015, Rabara et al, 2015a, Rabara et al, 2014a. Assessment of phenotypic diversity of 307 Philippine farmer-cultivated rice cultivars using a Shannon-Weaver diversity index (H') (Rabara et al, 2014a) showed low (average H'=0.45) and high (average H'= 0.73) diversity in qualitative and quantitative traits, respectively ( Figure 4B).…”
Section: Phenotyping and Genotyping Of Rice Genetic Resourcesmentioning
confidence: 99%
“…A well characterized germplasm with genetic different could be useful for their effective utilization. Genetic characterization at morphological and molecular level will enable rice breeders to exploit genotypic diversity for conservation and further crop improvement (Thomson et al, 2007;Juansa et al, 2012;Rabara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%